Answer:
On simplifying 11 m to the -5 , we get: [tex](\frac{1}{161051 \times m^5})[/tex]
Step-by-step explanation:
As we know by the law of EXPONENTS:
[tex]a ^{(-m)} = \frac{1}{a^m}[/tex]
Also, by the Power, w e get: [tex](a)^m = a \times a \times a ....... m[/tex] times
Here, using the same we find the value of : [tex](11m)^{(-5)}[/tex], we get:
[tex](11m)^{( -5)} = \frac{1}{(11m)^5} = \frac{1}{11m \times 11m \times 11m \times 11m \times 11m} = \frac{1}{161051 \times m^5} \\\implies (11m)^{( -5)} = \frac{1}{161051 \times m^5}[/tex]
Hence, on simplifying 11 m to the -5 , we get: [tex](\frac{1}{161051 \times m^5})[/tex]